PERDAGANGAN ANTAR PULAU SAPI BALI DARI TIMOR BARAT KE DKI JAKARTA - Johanis A. Jermias; Cardial Leo-Penu; Defrys R. Tulle; Tri A. Y. Foenay (Politeknik Pertanian Negeri Kupang, 2009)
A research was conducted for eight months to know trading system of Bali Cattle from Timor to DKI Jakarta and level ofÂ its body weight loses. Two hundred eighteen Bali Cattle were used in this research. The research was used survey and interview method to collect the data. Data were analyzed using Qualitative Descriptive Analysis and Proc. ANOVA (SAS institute, 2000) and further tested using Least Significant Diffrence (LSD). Results showed that trading system of Bali Cattle is begun from whole saler Jakarta send money to interisland tradesman then money is continued to collectors tradesman to buy cattle, furthermore cattle is sent by interisland tradesman to whole saler Jakarta later on sell cow to cutter or consumer at Jakarta. transportation tool that used truck colt diesel motor, boat (cargo), coupled truck, trintin tronton or trinton. The level of body weight loses was very high (8.53-17.30%) and of course it significant difference (P<0.01) for every Bali cattle came from. It is concluded that places of Bali cattle lived in give a different level of body weight losesKey words: trading, bali cattle, transportasion system, body weight loses